Mannose-Binding Lectin Levels and Carotid Intima-Media Thickness in Type 2 Diabetic Patients - Miklós Káplár; Shah Sweni; Julianna Kulcsár; Barbara Cogoi; Regina Esze; Sándor Somodi; Mária Papp; László Oláh; Mária Tünde Magyar; Katalin Szabó; Katalin Réka Czuriga-Kovács; Jolán Hársfalvi; et al. (Journal of Diabetes Research, 2016)
Introduction. Mannose-binding lectin (MBL) activates complement system and has been suggested to play a role in vascular complications in diabetics. Carotid intima-media thickness (cIMT) detects subclinical atherosclerosis. We evaluated the association of MBL and IMT in type 2 diabetic (T2DM) patients. Methods. Serum MBL levels and cIMT were measured in a total of 103 diabetics and in 98 age-matched healthy controls. Results. There was no significant difference in MBL level in T2DM versus controls. As expected, IMT was significantly higher in T2DM patients than in controls (P=0.001). In T2DM, the lowest cIMT was seen in patients with normal MBL level (500–1000) while cIMT continuously increased with both high MBL and absolute MBL deficiency states. This was especially significant in high MBL versus normal MBL T2DM patients (P=0.002). According to multiple regression analysis the main predictors of IMT in T2DM are age (P<0.003), ApoA level (P=0.023), and the MBL (P=0.036). Conclusions. Our results suggest a dual role of MBL as a risk factor for cIMT in T2DM. MBL may also be used as a marker of macrovascular disease, as both low and high levels indicate the susceptibility for atherosclerosis in T2DM.